(untitled) (Research, Society and Development, 2018)
This article aims to analyze the influence of cell phone on the productivity and organizational behavior of professionals in Belo Horizonte, and proposes a discussion about the benefits and harms of cell phone use in the daily life of individuals and institutions. Through an exploratory study of the perceptions of employees and managers and the orientation of the organizations in relation to technologies, the work is intended to understand the real influence of the tool. Based on the research carried out, the end result is that the tools are essential for professionals and companies in the scenario of constant evolution in which we live. However, the application of mobile phones in the business sphere still requires maturity and discipline to represent gains and competitiveness rather than dispersion.